2015
DOI: 10.1002/smll.201501083
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Helically Structured Chitin/CaCO3Hybrids through an Approach Inspired by the Biomineralization Processes of Crustacean Cuticles

Abstract: Chitin/CaCO3 hybrids with helical structures are formed through a biomineralization-inspired crystallization process under ambient conditions. Liquid-crystalline chitin whiskers are used as helically ordered templates. The liquid-crystalline structures are stabilized by acidic polymer networks which interact with the chitin templates. The crystallization of CaCO3 is conducted by soaking the templates in the colloidal suspension of amorphous CaCO3 (ACC) at room temperature. At the initial stage of crystallizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 65 publications
1
70
0
1
Order By: Relevance
“…Colloidal liquid crystals of crystalline polysaccharides can be used as templates to develop hybrid materials with helical structures showing mechanical toughness,t hat are environmental benign, and have optical functions. [199][200][201] CaCO 3 / polymer composites with helically ordered structures were prepared using colloidal chiral nematic liquid crystals of chitin nano-whiskers ( Figure 10). [199,200] Acidification of the chitin templates increase affinity between the organic templates and the inorganic components.I nn ature,t he cholesteric structures of chitin fibril, acidic proteins,and CaCO 3 are shown in the exoskeletons of crustaceans and these helical hybrid structures are responsible for the mechanical toughness of the composites.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Colloidal liquid crystals of crystalline polysaccharides can be used as templates to develop hybrid materials with helical structures showing mechanical toughness,t hat are environmental benign, and have optical functions. [199][200][201] CaCO 3 / polymer composites with helically ordered structures were prepared using colloidal chiral nematic liquid crystals of chitin nano-whiskers ( Figure 10). [199,200] Acidification of the chitin templates increase affinity between the organic templates and the inorganic components.I nn ature,t he cholesteric structures of chitin fibril, acidic proteins,and CaCO 3 are shown in the exoskeletons of crustaceans and these helical hybrid structures are responsible for the mechanical toughness of the composites.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Recently, stabilization of amorphous CaCO 3 by an acidic polymer and its promising application for the development of hybrid materials have been reported . We found that this stabilized amorphous CaCO 3 transformed into crystals on various polymer templates …”
Section: Introductionmentioning
confidence: 73%
“…[34,35] We found that this stabilized amorphous CaCO 3 transformed into crystals on various polymer templates. [36][37][38] Previously,w ed emonstrated that these methodso nt he formationo fC aCO 3 thin-film hybridsw ere applicable to other alkaline-earth carbonate compounds. [33,39,40] Crystallizationo f cobalt hydroxide [41] and manganese oxyhydroxide [42] have also been exploredb yu sing the diffusion of ammonium vapor.…”
Section: Introductionmentioning
confidence: 99%
“…Matsumura et al reported that a twisted plywood structure mimicking lobster cuticle could be constructed via a template of cholesteric liquid crystal (LC) formed from chitin whisker. [59] A more universal and controllable method, however, is magnetically assisted slip casting (MASC) [60] or magnetically assisted 3D printing. [61,62] Ferrand et al [60] demonstrated that alumina nanoplatelets coated with superparamagnetic iron oxide nanoparticles could be assembled by applying an external rotating magnetic field.…”
Section: Mimicking Of Architecturementioning
confidence: 99%